ATIVIDADES DE EXTENSÃO PARA PEQUENAS EMPRESAS E COOPERATIVAS DA REGIÃO DE ABRANGÊNCIA DA UNIJUÍ - Enderli, Stela M.; Steinbrenner, Anélia F.; Brizolla, Maria M.; Barth, Vanessa; Markoski, Deise Z. N. (Salão do Conhecimento, 2013)
Resumo